Lived experiences of human immunodeficiency virus and hypertension in the Eastern Cape, South Africa - Lwandile Tokwe; Joanne R. Naidoo (AOSIS, 2020)
Background: Globally, the healthcare system is burdened with the rise in communicable diseases compounded by the comorbidity of non-communicable diseases. South Africa in particular experiences a quadruple burden of diseases, and human immunodeficiency virus (HIV) and hypertension are amongst the burden of diseases reported. Aim: This article aims to explore and describe the lived experiences of people living with HIV (PLWH) and hypertension in the Eastern Cape, South Africa. Setting: The study was conducted in the Sakhisizwe sub-district within the Chris Hani health district of the Eastern Cape. Methods: A qualitative study design using Husserl's descriptive phenomenology underpinned this study. Purposive sampling method was used to select participants. Information was gathered using semi-structured interviews from nine participants who met the inclusion criteria. The interviews were recorded on an audiotape and conducted in isiXhosa, and these were verified through back and forward translation to English. The transcribed interviews were coded manually, and underpinned by Giorgi's phenomenological data analysis steps. Results: This study yielded four themes that described the journey towards a new normal experienced by participants. These themes were (1) overcoming illness-related stigma, (2) sources of support, (3) self-love: taking ownership of the diseases and (4) creating transforming behaviours and self-care strategies. Conclusion: This study demonstrated that the central theme that emerged from the lived experiences of participants with HIV and hypertension was a process of finding a new normal for their lives. This process had several enabling and inhibiting conditions that enabled participants to develop self-acceptance and find strategies to transform behaviours to better live with two chronic illnesses.